The Relationship of Teacher Pedagogic Abilities With Student Learning Interest - Kusharyadi, Rahmat; Herman, Tatang; Pauji, Ikbal; Dewantara, M.O.G (Universitas Sebelas Maret, 2023)
This study was conducted in SMPN 1 Cileungsi, the purpose of which was to analyze the pedagogical competence of mathematics teachers together with the learning interests of students based on predetermined indicators. The method used in this study is a quantitative method. Sampling was done using probability sampling by simple random sampling technique so that 100 samples were obtained. Based on the results of the Amos plot, the Chi-square value is 765.652, the probability value is 0.000, the GFI value is 0.662, the AGFI value is 0.612, the TLI value is 0.457, and the RMSEA value is 0.095. A -value of 0.004 is obtained, which is less than = 0.05, so it has the interpretation that there is a significant effect between pedagogical competence and learning interest of students and between pedagogical competence and 1000 learning interest. and the total effect is 2007.